REPRESENTASI VIKTIMISASI PEREMPUAN DALAM HUBUNGAN ROMANTIS PADA FILM LIKE & SHARE (2022) - Adrian Budynata, Johan; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
The high incidence of dating violence and the higher number of women as victims serve as the background for this research. This study aims to examine how the film "Like & Share" (2022) represents the victimization of women in romantic relationships. Using standpoint theory, the research seeks to explore the depiction and uncover the ideologies and messages that the filmmakers intend to convey. The findings show that the film "Like & Share" represents the victimization of women through the interactions and actions of the characters in the film, depicted in various forms such as primary, secondary, and structural victimization. The portrayal of women's victimization in romantic relationships in this film demonstrates efforts to subjugate women by men or third parties driven by men who want to assert their superiority in the relationship. Additionally, the stereotypes and stigmas of women as victims in this film are also highlighted as representations of women's victimization in romantic relationships because they can cause additional suffering, especially from a psychological aspect. Through this film, the reinforcement of women's position as the subordinate group and men in the superior position can occur. It is hoped that society, especially men, will become more wise in addressing this issue of victimization.